1999
DOI: 10.1007/s005860050140
|View full text |Cite
|
Sign up to set email alerts
|

Cervical electromyographic activity during low-speed rear impact

Abstract: IntroductionRear-end collisions typically occur in dense traffic at very low speeds. The vehicle is subjected to a forward acceleration during which the occupants are pushed forward by the seatbacks. The head lags behind forcing the neck into extension. This head motion continues until the neck hits the headrest or reaches its maximum range of motion, or is counteracted by the muscles. The head then reacts by moving forward into a flexed neck posture. This is the typically described injurious extension-flexion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 10 publications
7
76
0
Order By: Relevance
“…Magnusson et al [11] did not report significant differences in cervical muscle reaction times between expected and unexpected conditions. Kumar et al [9] reported lower SCM EMG activity in expected impacts.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Magnusson et al [11] did not report significant differences in cervical muscle reaction times between expected and unexpected conditions. Kumar et al [9] reported lower SCM EMG activity in expected impacts.…”
mentioning
confidence: 89%
“…Among the cervical muscles, the sternocleidomastoid (SCM) muscle might play a significant role in whiplash injury [2,9,11,13,16]. Magnusson et al [11] did not report significant differences in cervical muscle reaction times between expected and unexpected conditions.…”
mentioning
confidence: 99%
“…Given ethical concerns with subjecting volunteers to injurious neck perturbations, most volunteer experiments have, for example, been conducted with military personnel and members of the research team. A few other experiments have been done with other volunteer groups but were necessarily limited to low-or very low-velocity collisions [1,3,4,7,9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…[4, p. 331). Yet, on the basis of studies showing that the neck does not move beyond the physiological range for lowvelocity impacts [9,10,15,16] and that an eccentric muscle contraction occurs in response to impacts [9], muscle injury remains the most likely candidate for site of tissue injury. Only through more dedicated imaging protocols is the muscle sprain likely to be captured, but part of the process of understanding where to look for the whiplash injury may begin with whiplash experiments pointing to the tissues at greatest risk for injury.…”
Section: Discussionmentioning
confidence: 99%
“…This body of research has been primarily motivated by a desire to prevent or lessen the extent of whiplash injury, and is, for example, the basis for the introduction in 1969, of the head restraint [13]. Based on human research [5][6][7][8][9][10][11][12]15,16], it has been suggested that for rear-end impacts we can understand the injury mechanism to be a whip's lash, in the very sense that Crowe first postulated when he coined the term whiplash in 1928 [2].…”
Section: Introductionmentioning
confidence: 99%